Wage Implications of Trade Liberalisation Evidence for Effective Policy Formation - Stone, Susan (OECD Publishing, 2011)
The relationship between trade and wages has been subject to intense scrutiny in the academic literature with no clear consensus emerging. This paper adds to this body of research by moving beyond the single country analysis level to a panel including developed and developing countries and data through the mid 2000.s. First we examine the relationship between wages and trade using the approach of Feenstra and Hanson to calculate mandated wage changes for our dataset. We find that imports have a significant and positive impact on wages while the sign on tariffs is negative and significant. We also look at the relationship of wage differentials at the occupation level between partner countries. We find that the difference in occupation wage is smaller for large trade partners. Finally, we discuss the potential role of NTMs in influencing the wage and trade relationship
Keywords: Trade